PENYUSUNAN INSTRUMEN PENILAIAN RANAH AFEKTIF BERBASIS KURIKULUM 2013 DI SEKOLAH DASAR - Jenny Indrastoeti SP; Ismail Ismail; yulianti yulianti (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2015)
This article is written based on the community service program done by lectures of FKIP UNS. This program is aimed at improving professionalism of primary teachers in Surakarta Regency by holding affective assessment workshop based on 2013 curriculum. This workshop prepares all needs on preparing affective assessment instruments, including theoretical based, outline on planning instruments and rubric.  This methods used in this workshop are training and coaching. They are some facts found during the workshop. They are primary teachers have lack competence on preparing affective assessment instruments, developing ideas on written affective indicator, planning blue print and rubric.